Accuracy of Ophthalmology Clinic Follow-Up in the Incarcerated Patient Population - Michelle M. Abou-Jaoude; Jessica Crawford; Richard J. Kryscio; Daniel B. Moore (Journal of Academic Ophthalmology, 2022)
Purpose Incarcerated patients represent a uniquely vulnerable population in the outpatient ophthalmology setting, and the reliability of follow-up in this group is undetermined. Methods This was a retrospective, observational chart review of consecutive incarcerated patients evaluated at the ophthalmology clinic of a single academic medical center between July 2012 and September 2016. For each encounter the following were recorded: patient age, gender, incarcerated status at the time of encounter (a subset of patients had encounters before/after incarceration), interventions performed, follow-up interval requested, urgency of follow-up, and actual time to subsequent follow-up. Primary outcome measures were no-show rate and timeliness, which was defined as follow-up within 1.5× the requested period. Results There were 489 patients included during the study period, representing a total of 2,014 clinical encounters. Of the 489 patients, 189 (38.7%) were seen once. Of the remaining 300 patients with more than one encounter, 184 (61.3%) ultimately did not return and only 24 (8%) were always on time for every encounter. Of 1,747 encounters with specific follow-up requested, 1,072 were considered timely (61.3%). Factors significantly associated with subsequent loss to follow-up include whether a procedure was performed (p < 0.0001), urgency of follow-up (p < 0.0001), incarcerated status (p = 0.0408), and whether follow-up was requested (p < 0.0001). Conclusion Almost two-thirds of incarcerated patients in our population requiring repeat examination were lost to follow-up, particularly those who underwent an intervention or required more urgent follow-up. Patients entering and exiting the penal system were less likely to follow-up while incarcerated. Further work is needed to understand how these gaps compare to those in the general population and to identify means of improving these outcomes.